2006
DOI: 10.1093/chromsci/44.7.444
|View full text |Cite
|
Sign up to set email alerts
|

The Extraction and Analysis of 1,4-Dioxane from Water Using Solid-Phase Microextraction Coupled with Gas Chromatography and Gas Chromatography--Mass Spectrometry

Abstract: In this study, two methods are developed for the extraction of 1,4-dioxane (dioxane) from water using 80-microm carboxen-polydimethylsiloxane solid-phase microextraction fibers followed by either gas chromatography (GC)-flame ionization detection (FID) or GC-mass spectrometry (MS). With GC-FID, the lower limit of detection (LOD) for 1,4-dioxane is 2.5 microg/L (ppb) with a linear range of 5 to 10,000 microg/L, obtained by immersing the fiber in the sample for 20 min with agitation. Using GC-MS, the lower limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 7 publications
1
12
0
Order By: Relevance
“…The MDL determined in this study falls well below the Michigan drinking water standard in groundwater of 7.2 μg/L but is higher than the federal health risk guideline of 0.35 μg/L for drinking water [2]. The MDL compares well with other methods that utilize LLE, SPE, and Purge and Trap (P&T) sample preparation methods listed in Table 1 [19–23].…”
Section: Resultsmentioning
confidence: 57%
“…The MDL determined in this study falls well below the Michigan drinking water standard in groundwater of 7.2 μg/L but is higher than the federal health risk guideline of 0.35 μg/L for drinking water [2]. The MDL compares well with other methods that utilize LLE, SPE, and Purge and Trap (P&T) sample preparation methods listed in Table 1 [19–23].…”
Section: Resultsmentioning
confidence: 57%
“…C 4 H 8 O 2 is not biodegradable and was classified as a potential carcinogen by the US Environmental Protection Agency (EPA). Widely used as an industrial solvent, C 4 H 8 O 2 is considered as the major anthropogenic source of 1,4-dioxane in the atmosphere [ 89 , 90 ]. Chandran et al [ 65 ] reported a novel FT-IBBCEAS to record the absorption of C 4 H 8 O 2 in the spectral range of 5900−8230 cm −1 with a resolution of 0.08 cm −1 .…”
Section: Target Gas Species Performances In Laboratorymentioning
confidence: 99%
“…[13][14][15][16][17][18][19] Recently, a specific and highly sensitive headspace solid phase microextraction (SPME) [20][21][22][23] and a isotopic dilution headspace (IDHS) 24 …”
Section: -12mentioning
confidence: 99%